Indonesian Muslim killings: revisiting the forgotten Talang Sari tragedy (1989) and its impact in post authoritarian regime - Wahyudi Akmaliah (IAIN Salatiga, 2016)
Although the Talang Sari tragedy as a part of the representation of Indonesian Muslim oppression during the authoritarian regime, it is relatively lesser known for Indonesian public. The avoidance of the most Indonesian Muslim who did not support it is one of those facts. Indeed, they did a less attention to talk and to articulate the case to the public. This paper intends to revisit the case of the Talang Sari as one of the unsolved human rights violation during the authoritarian regime. It is not only exploring the case and also examining the context of violence, but also tracing dynamic of the case during and post of authoritarian regime by the emergence of Islah agreement as cultural impu- nity to forget the past for many victims. The questions deals with in this paper are following: what kind of conditions that made the Talang Sari was happen- ing in East Lampung in 1989, South Sumatra during the Suharto presidency? How did the Suharto regime control the discourse of the tragedy in Indone- sian public that eventually encourage most Indonesian Muslim did not actively respond the killings? Although the reformasi era gives an opportunity break silences by asking justice to the current Indonesian government on hu- man rights violation, why those cases, especially the Talang Sari, are unsolved? This paper divided into three parts to answering the questions. Firstly, it is to understand the case of Talang Sari by discussing the context of the New Order’s policy on Indonesian Muslim and its political ideology. Secondly, it is to read deeply mass media in making discourse on the case as one of the triggers for most Indonesian Muslim did not respond it. Thirdly, it is to analyze the Islah agreement (reconciliation in Islamic term) as the primary factor that contrib- uted why cultural impunity has seemingly embedded to bring justice to the victims of violence generally in the post of Suharto regime. Meskipun Peristiwa Talang Sari sebagai bagian dari representasi penindasan masyarakat Muslim Indonesia selama rejim otoriter berkuasa, peristiwa itu jarang diketahui oleh publik Indonesia. Pengabaian kebanyakan Muslim Indo- nesia yang tidak mendukung upaya penyelesaian kasus tersebut adalah salah satu buktinya. Bahkan, mereka tidak membicarakan dan mengangkat kasus Talang Sari di ruang publik. Artikel ini bermaksud melihat kembali peristiwa Talang Sari sebagai salah satu kasus pelanggaran yang belum diselesaikan. Selain mengeksplorasi kasus, menjelaskan konteks kekerasan, artikel ini juga menelusuri dinamika kasus tersebut sebelum dan pasca rejim Orde Baru, khususnya seiring dengan kemunculan Islah sebagai Impunitas Kultural untuk melupakan masa lalu oleh sebagaian korban. Pertanyaannya yang diajukan dalam artikel ini adalah: kondisi-kondisi semacam apa yang membuat kasus Talang Sari terjadi di Lampung Timur pada tahun 1989, Sumatera Selatan saat presiden Suharto berkuasa? Bagaimana rejim Suharto mengontrol wacana peristiwa tersebut yang membuat kebanyakan masyarakat Islam Indonesia tidak menanggapi peristiwa tersebut? Meskipun pasca rejim Orde Baru memberikan kesempatan untuk menyelesaikan kasus tersebut dengan mendesak untuk mengajukan keadilan kepada pemerintah Indonesia, mengapa peristiwa Talang Sari tidak atau belum diselesaikan hingga sekarang?. Untuk menjawab pertanyaan-pertanyaan tersebut, saya membagi penjelasan ini kepada tiga bagian. Pertama, memahami kasus Talang Sari dengan mendiskusikan konteks kebijakan rejim Orde Baru dalam menghadapi umat Islam dan ideologi politiknya. Kedua, membaca lebih dalam media cetak dalam membuat wacana peristiwa tersebut melalui liputan yang dibuat. Asumsi ini diajukan karena liputan media tersebut menjadi salah satu penyebab mengapa kebanyakan umat Islam tidak merespon peristiwa tersebut. Ketiga, menganalisis persetujuan Islah, rekonsiliasi dalam perspektif Islam sebagai faktor utama yang memberikan kontribusi terhadap impunitas kultural untuk membawa keadilan ke jalan yang lebih sulit kepada korban secara umum pasca rejim Suharto.